IMMUNOHISTOCHEMICAL ANALYSIS OF CASPASE-3 ACTIVITY IN LIVER BIOPSIES OF PATIENTS WITH MONO AND MIXED INFECTIONS - I. I. Tokin; I. B. Tokin; T. V. Sologub; G. F. Filimonova; P. Hussar (Klinicist)
Objective: to study the activity of proapoptotic signal protein caspase-3 for determination of peculiarities of apoptosis regulation under liver chronic diseases.Subjects and methods. The immunohistochemical analysis of caspase-3 activity in 5 liver biopsies of the patients with mono infection of chronic hepatitis B and 5 liver biopsies of the patients with mixed infection of tuberculosis, chronic hepatitis C and human immunodeficiency virus was fulfilled. Morphological and morphometric analysis of serial microphotographs was performed using an image analysis system (microscope Leica DM 2500, digital camera Leica DFC320 R2 and a computer).Results. The activity of caspase-3 as dark brown granularity was revealed in all tis-sue components of liver (hepatocytes, epithelium of bile ducts, endotheliocytes, Kupffer cells of sinusoids, in compositions of lymphohistiocyte infiltrations). The maximal activity was discovered in hepatocytes nuclei. The expression of caspase-3 was significantly higher in liver biopsies of the patients with mixed infection. It is typical that the immunoreactive hepatocytes had not any morphological marks of apoptosis.Conclusion. The caspase-3 expression of proapoptotic signal protein caspase-3 may serve as an early marker of liver damage including the possibilities of apoptosis development.